Comparing volume-clamp method and intra-arterial blood pressure measurements in patients with atrial fibrillation admitted to the intensive or medium care unit. - Berkelmans, G. F. N.; Kuipers, S.; Westerhof, B. E.; Spoelstra-De Man, A. M. E.; Smulders, Y. M. (Journal of Clinical Monitoring & Computing, 2018)
International guidelines highlight the importance of blood pressure (BP) in patients with atrial fibrillation (AF). However, BP measurement in AF is complicated by beat-to-beat fluctuation. Automated BP measurement devices are not validated for patients with AF and no consensus exists on how to measure BP in AF manually. Beat-to-beat BP measurement using the volume-clamp method (VCM) could represent a non-invasive method to accurately assess BP, but has not been validated in AF. 31 admitted patients with sustained AF and 10 control patients with sinus rhythm underwent simultaneous intra-arterial and non-invasive BP measurement using a VCM monitor (Nexfin®, BMEYE, Amsterdam, The Netherlands). Patients with compromised peripheral perfusion, high doses of vasopressor drugs or peripheral edema were excluded. Differences in systolic, diastolic and mean BP of 5 (standard deviation; SD 8) mmHg (accuracy and precision) between both methods were considered acceptable. Additionally, the magnitude of beat-to-beat fluctuations in systolic BP of both methods was compared. In AF, the differences between noninvasive and invasive BP were -4 (SD 12), +1 (SD 7) and 0 (SD 8) mmHg for systolic, diastolic and mean BP respectively. Absolute differences in beat-to-beat BP fluctuations were 1.5 (IQR 0.8-3.8) mmHg. Accuracy of VCM in AF was similar to sinus rhythm. In conclusion, in patients with AF, accurate and precise measurement of non-invasive beat-to-beat BP measurement using the VCM is possible, the one exception being the precision of systolic BP. Beat-to-beat variability can be accurately reproduced.